2012
DOI: 10.1055/s-0032-1301920
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of Frataxin in Pancreatic Islets Isolated from Multi-Organ Donors with and Without Type 2 Diabetes Mellitus

Abstract: Frataxin (FXN) is a mitochondrial protein involved in iron metabolism and in the modulation of reactive oxygen and/or nitrogen species production. No information is currently available as for the role of frataxin in isolated human pancreatic islets. We studied islets from pancreases of multi-organ donors with (T2DM) and without (Ctrl) Type 2 diabetes mellitus. In these islets, we determined FXN gene and protein expression by qualitative and quantitative Real-Time RT-PCR, nitrotyrosine concentration, and insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Frataxin‐deficient INS‐1E cells tended to have increased insulin content (Fig 4), suggesting that frataxin deficiency does not impair insulin synthesis in β cells. The knockdown did not modify basal insulin secretion, but it reduced glucose‐ or glucose + forskolin‐stimulated insulin secretion, in keeping with recent findings in human islets 46. Glucose‐stimulated ATP production, which regulates insulin secretion, was impaired in frataxin‐deficient β cells.…”
Section: Resultssupporting
confidence: 88%
“…Frataxin‐deficient INS‐1E cells tended to have increased insulin content (Fig 4), suggesting that frataxin deficiency does not impair insulin synthesis in β cells. The knockdown did not modify basal insulin secretion, but it reduced glucose‐ or glucose + forskolin‐stimulated insulin secretion, in keeping with recent findings in human islets 46. Glucose‐stimulated ATP production, which regulates insulin secretion, was impaired in frataxin‐deficient β cells.…”
Section: Resultssupporting
confidence: 88%
“…The presence of oxidative stress 3, 37 and increased expression of UPR pathway factors such as CHOP 14 has been observed in islets from type 2 diabetic individuals. We investigated if proapoptotic molecules are also upregulated in human type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…The knockdown did not modify basal insulin secretion, but it reduced glucose-or glucose + forskolin-stimulated insulin secretion, in keeping with recent findings in human islets. 46 Glucose-stimulated ATP production, which regulates insulin secretion, was impaired in frataxin-deficient β cells. In addition, frataxin depletion reduced mitochondrial membrane potential in β cells (Supplementary Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…5456 Of note, it was recently shown that islets from T2D donors have lower frataxin mRNA and protein expression. 46 The cause(s) of β -cell dysfunction/death in T2D is not well understood; genetic and environmental factors including sedentary lifestyle and energy-dense diets contribute. Abdominal obesity has been linked to loss of β -cell function in T2D, 54,57 and FFAs may mediate this deleterious effect.…”
Section: Discussionmentioning
confidence: 99%